The Development of Science Technology, Engineering and Mathematics-Based Digital Comic of Number Patterns for Mathematics Learning - Khairunnisa Khairunnisa; Nurazizah; Maifalinda Fatra; Khamida Siti Nur Atiqoh (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2024)
Abstract: Pengembangan media digital tidak hanya menunjang proses pembelajaran tetapi juga membuat pembelajaran mengikuti perkembangan teknologi terkini. Penelitian ini bertujuan untuk mengembangkan komik digital berbasis STEM. Penelitian ini merupakan jenis penelitian pengembangan. Model pengembangan yang digunakan adalah model ADDIE yang terdiri dari lima tahap yaitu analisis, desain, pengembangan, implementasi, evaluasi. Produk yang dikembangkan adalah komik digital berbasis STEM pada materi pola bilangan. Hasil validasi ahli media dan ahli materi menunjukkan bahwa produk komik digital berbasis STEM ini valid dan layak digunakan. Penggunaan komik digital berbasis STEM dalam kegiatan pembelajaran memperkenalkan cara baru dan inovatif untuk mempelajari pola bilangan dan dapat membantu siswa memahami konsep dengan lebih efektif. Komik digital berbasis STEM ini juga mendapat respon positif dari siswa dengan kriteria layak. Abstrak: The development of digital media not only supports the learning process but also keeps up with the latest technological developments. This  study  aims  to  develop  a  STEM-based  digital comic.  This  study  is  a  type  of  development  research.  The  development  model  used  is  the ADDIE model, which consists of five stages, namely, analysis, design, development, implementation, evaluation. The product developed are STEM-based digital comic focusing on number patterns. The results of the validation of media and material experts indicate that this STEM-based digital comic product is valid and feasible to use. The use  of  STEM-based digital comic in  learning  activities  introduced a new and innovative way to learn number patterns and could help the students understand the concept more effectively.  This  STEM-based  digital comic also gets positive responses from students with feasible criteria.